Free but Not Fair? Analyzing the Implementation of Free Education Policy in Malang City through a Justice-Oriented Framework - Zahroh, Viony Alfiyatu (PANGRIPTA, 2025)
This study examines the implementation of a free education policy in Malang City, Indonesia, and its implications for equity in access and outcomes. Although the policy guarantees uniform financial assistance for all students in public elementary and junior high schools, its execution reveals substantial gaps between the promise of equality and the lived experiences of students, particularly those from disadvantaged backgrounds. Based on qualitative data gathered through interviews, document analysis, and field observations, the study identifies three major challenges. First, the interpretation of “free education” varies across schools, leading to inconsistencies in application and confusion among beneficiaries. Second, limitations in bureaucratic coordination, technical capacity, and communication contribute to inefficiencies in fund distribution and reporting. Third, the flat-rate subsidy fails to account for indirect costs borne disproportionately by low-income families, such as transportation, uniforms, and extracurricular participation. The findings suggest that the policy’s universal design, while administratively efficient and politically popular, does not ensure equitable outcomes. Without mechanisms for targeting or flexibility, students most in need may continue to face barriers to full participation in schooling. To address these issues, the study recommends context-sensitive reforms that combine universal access with additional support for vulnerable groups. It also calls for stronger institutional feedback loops and school-level autonomy in addressing local needs. In conclusion, achieving meaningful educational access requires a shift in perspective—from providing the same for all, to ensuring success for those who need more.